Spinal Anestesi Pada Tindakan Transuretral Resection Of Prostat (TURP) - Atika Fadhilla; Abrar Abrar (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2024)
Spinal anesthesia is the choice for Transurethral Resection of Prostate (TURP) procedures. TURP is a surgical procedure performed for patients with prostatic hyperplasia. When a TURP procedure is performed, excessive fluid absorption will occur because during the procedure the injured area causes the vein to open and irrigation fluid will be absorbed. The position of the surgical procedure in the lithotomy position makes the situation worse. Spinal anesthesia helps peripheral blood collection and reduces circulatory overload, early detection of TURP syndrome and bladder perforation. In this case, the procedure was carried out on a 67 year old man with a diagnosis of benign prostate hyperplasia (BPH) with a TURP surgical procedure. The patient was composmentis, ASA III. The patient underwent spinal anesthesia with a sub arachnoid block using Bupivacaine. During TURP procedures, TURP syndrome can occur which is influenced by the use of fluid as irrigation to widen the operator's field of view. Saline fluid should be used, but because it is expensive, H2O is often used as irrigation fluid. A complication of the TURP procedure is TURP syndrome